2019
DOI: 10.1210/jc.2019-00029
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Radiation Improves Recurrence-Free Survival and Overall Survival in Adrenocortical Carcinoma

Abstract: Context Adrenocortical carcinoma (ACC) is a rare malignancy with high rates of recurrence and poor prognosis. The role of radiotherapy (RT) in localized ACC has been controversial, and RT is not routinely offered. Objective To evaluate the benefit of adjuvant RT on outcomes in ACC. Design This is a retrospective propensity-matched analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 30 publications
1
32
0
1
Order By: Relevance
“…In a meta-analysis, adjuvant radiotherapy had a significant benefit on local recurrence (RR, 0.24; 95% CI, 0.12-0.49), but no effect on disease survival and OS [67]. Most recently, a single-institution, propensity-matched retrospective analysis evaluated adjuvant XRT and found that using adjuvant XRT was associated with improved local RFS, all RFS, and OS [68]. So far, there is no prospective data to ascertain the value of adjuvant radiotherapy and findings of retrospective data need to be carefully interpreted because of the potential of referral and selection biases.…”
Section: Adjuvant Radiotherapymentioning
confidence: 99%
“…In a meta-analysis, adjuvant radiotherapy had a significant benefit on local recurrence (RR, 0.24; 95% CI, 0.12-0.49), but no effect on disease survival and OS [67]. Most recently, a single-institution, propensity-matched retrospective analysis evaluated adjuvant XRT and found that using adjuvant XRT was associated with improved local RFS, all RFS, and OS [68]. So far, there is no prospective data to ascertain the value of adjuvant radiotherapy and findings of retrospective data need to be carefully interpreted because of the potential of referral and selection biases.…”
Section: Adjuvant Radiotherapymentioning
confidence: 99%
“…us, controlling the signals associated with radiation-induced resistant genes might be a major strategy in radiotherapy to reduce the irradiation burden in the host [10,11]. For this reason, the discovery of adjuvants targeting radioresistant molecules is important for effective radiotherapy [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The local recurrence rate of adjuvant RT group was signi cantly reduced to 5% vs. 60% of non-RT group, although there was no difference in OS. The largest study [30] on this subject included 39 patients with a median irradiation does of 55Gy, and found that adjuvant RT signi cantly improved the local recurrence (33.3% vs. 71.8%) and OS (77.7% vs. 48.6% at 3 years). In the present study, only 16.7% patients in adjuvant RT group experienced local recurrences, which was signi cantly lower than 51.7% in non-RT group.…”
Section: Discussionmentioning
confidence: 99%